THE INVOLVEMENT OF ORGANIZATIONS IN KNOWLEDGE MANAGEMENT - Alin NIOAŢĂ (Fiabilitate şi Durabilitate)
Explicit knowledge management by distributing and storing knowledge in different ways promotes updating and further development of knowledge, skills and competence, namely it promotes learning. In addition, knowledge management encourages employees to share their experiences and knowledge, to teach each other in formally or informally structured activities in daily activities. In this way, knowledge management facilitates the creation of an environment that makes it possible knowledge through which are created conditions for the development of skills and competencies.